Copy number variation in CEP57L1 predisposes to congenital absence of bilateral ACL and PCL ligaments. Issue 1 (December 2015) - Liu, Yichuan; Li, Yun; March, Michael; Nguyen, Kenny; Xu, Kexiang; Wang, Fengxiang; Guo, Yiran; Keating, Brendan; Glessner, Joseph; Li, Jiankang; Ganley, Theodore; Zhang, Jianguo; et al.
Abstract Background Absence of the anterior (ACL) or posterior cruciate ligament (PCL) are rare congenital malformations that result in knee joint instability, with a prevalence of 1.7 per 100, 000 live births and can be associated with other lower-limb abnormalities such as ACL agnesia and absence of the menisci of the knee. While a few cases of absence of ACL/PCL are reported in the literature, a number of large familial case series of related conditions such as ACL agnesia suggest a potential underlying monogenic etiology. We performed whole exome sequencing of a family with two individuals affected by ACL/PCL. Results We identified copy number variation (CNV) deletion impacting the exon sequences ofCEP57L1, present in the affected mother and her affected daughter based on the exome sequencing data. The deletion was validated using quantitative PCR (qPCR), and the gene was confirmed to be expressed in ACL ligament tissue. Interestingly, we detected reduced expression ofCEP57L1 in Epstein–Barr virus (EBV) cells from the two patients in comparison with healthy controls. Evaluation of 3D protein structure showed that the helix-binding sites of the protein remain intact with the deletion, but other functional binding sites related to microtubule attachment are missing. The specificity of the CNV deletion was confirmed by showing that it was absent in ~700 exome sequencing samples as well as in the database of genomic variations (DGV), a database containing large numbers of annotated CNVs from previous scientific reports. Conclusions We identified a novel CNV deletion that was inherited through an autosomal dominant transmission from an affected mother to her affected daughter, both of whom suffered from the absence of the anterior and posterior cruciate ligaments of the knees.